Impact analysis of emulsified Calophyllum oil biodiesel B100-WIC and B50-WIC on performance and emission characteristic of a diesel engine under variation in compression ratio. Issue 1 (31st December 2022) - Bawane, Rahul Krishnaji; Muthuraja, A.; Shelke, Gajanan N.; Choudhary, Chetan
Abstract : The present experimental investigation is carried out to analyse the impact of water inclusion (10 vol.%) in Calophyllum biodiesel under the variation of compression ratio (CRs). The objective of this work is to test higher biodiesel blend B50 with inclusion of water to optimise diesel engine performance and exhaust emissions. The investigation revealed, B50-WIC gives the most favourable results, whereas B100-WIC reported outcomes in between that of B100 and B50-WIC. The findings reported that inclusion of water reduced the NO x emission level and shows improvement in brake thermal efficiency (BTH). At CR ratio 17:1 concluded emulsified fuel B50-WIC is the best fuel blend. B50-WIC in reference to neat diesel there is increased in, BSEC with 79%, and reduction in BTH, EGT, CO, CO2, and most importantly NO x with 10.39%, 3.71%, 17.07%, 5.76%, 20.97% respectively. But there is no change reported for HC. The B50-WIC in reference to B100 there is an increased in BTH, EGT, CO, HC, CO2, and NO x with 21.56%, 4.26%, 9.68%, 16.67%, 2.46%, and 5.77% respectively and BSEC reduction by 50%.